2018
DOI: 10.1016/j.dental.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Shining a light on high volume photocurable materials

Abstract: Spatial and temporal control is a key advantage for placement and rapid setting of light-activated resin composites. Conventionally, placement of multiple thin layers (<2mm) reduces the effect of light attenuation through highly filled and pigmented materials to increase polymerisation at the base of the restoration. However, and although light curing greater than 2mm thick layers is not an entirely new phenomenon, the desire amongst dental practitioners for even more rapid processing in deep cavities has led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 77 publications
(88 reference statements)
0
64
0
4
Order By: Relevance
“…In addition to the refractive index, also the filler dimension exerts a significant effect on light scattering, that was shown to be highest when the filler diameter approaches approximately one-half the wavelength of incident light, i.e. ~0.2-0.3 µm [3]. It must also be noted that large variation in light transmission was observed also within resin composite of similar shade [15].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to the refractive index, also the filler dimension exerts a significant effect on light scattering, that was shown to be highest when the filler diameter approaches approximately one-half the wavelength of incident light, i.e. ~0.2-0.3 µm [3]. It must also be noted that large variation in light transmission was observed also within resin composite of similar shade [15].…”
Section: Introductionmentioning
confidence: 97%
“…The optical properties of light cured resin-based composites (RBC) are essential material characteristics that are relevant for both the esthetical appearance of a restoration [1,2] and the quality of curing in depth [3]. The latter is fundamentally related to the translucency of the material and thus to the amount of light (photons) that is allowed to pass through the RBC during polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Exponential growth of photopolymerization applications have been witnessed in the last decade: from historical niche coatings markets, it has spread out into additive manufacturing (three‐dimensional [3D] printing), biomaterials, composites, adhesives, graphic arts, thick specimen manufacturing, dental materials, and so on . This ever growing applications require the development of environmental‐friendly photopolymerization processes to cope with ever increasing environmental pressure, this is more and more studied with naturally derived monomers .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the dentist should be aware that the irradiance of an LCU diminishes as the distance increases from the light output window [6] and, besides that, the cleanliness aspect of the LCU light tip is fundamental, because any residual RBC stuck onto the light exiting window may also reduce the light irradiance, which is a huge problem that affects the geometry of the light tip which may create shadows [7,8], and thus the depth of the cure may be reduced. Furthermore, depending on their composition (filler, resin mix, pigments and opacifiers), RBCs absorb more or less light [9], which reduces the depth of the cure as well. Based on this knowledge, recommendations for dentists about how to light cure were formulated by a group of researchers, industry representatives, editors and dentists [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that the LCUs as used in practices do not yield the light intensity output stated by the manufacturers [13][14][15][16]. The outcome of light curing can be influenced as well by factors which are governed by the design of the LCU and of course by the RBCs themselves [9,17]. The characteristics of the LCUs have a strong influence on the incident irradiance received by a material due to a multitude of…”
Section: Introductionmentioning
confidence: 99%